Answer:
$ 338.70
Step-by-step explanation:
https://www.calculatorsoup.com/calculators/financial/loan-calculator-simple.php?pv=15%2C000.00&ratepercent=4&t=48&time_t=month&given_data_last=find_pmt&action=solve
Answer:
6 feet
Step-by-step explanation:
(24+x)(16+x)=660
384+24x+16x+x²=660
x²+40x-276=0
x`= 6
x```= -46......no serve
Answer......is 6 feet
Answer:
5 percent.
Step-by-step explanation:
Divide tax by the cost to see the percentage of the tax.
750/37.50=0.05
5 percent.
The distance formula is an algebraic expression used to determine the distance between two points with the coordinates (x1, y1) and (x2, y2).
<span><span>D=<span><span>(<span>x2</span>−<span>x1</span><span>)2</span>+(<span>y2</span>−<span>y1</span><span>)2</span></span><span>−−−−−−−−−−−−−−−−−−</span>√</span></span><span>D=<span>(<span>x2</span>−<span>x1</span><span>)2</span>+(<span>y2</span>−<span>y1</span><span>)2</span></span></span></span>
Example
Find the distance between (-1, 1) and (3, 4).
This problem is solved simply by plugging our x- and y-values into the distance formula:
<span><span>D=<span><span>(3−(−1)<span>)2</span>+(4−1<span>)2</span></span><span>−−−−−−−−−−−−−−−−−−</span>√</span>=</span><span>D=<span>(3−(−1)<span>)2</span>+(4−1<span>)2</span></span>=</span></span>
<span><span>=<span><span>16+9</span><span>−−−−−</span>√</span>=<span>25<span>−−</span>√</span>=5</span><span>=<span>16+9</span>=25=5</span></span>
Sometimes you need to find the point that is exactly between two other points. This middle point is called the "midpoint". By definition, a midpoint of a line segment is the point on that line segment that divides the segment in two congruent segments.
If the end points of a line segment is (x1, y1) and (x2, y2) then the midpoint of the line segment has the coordinates:
<span><span>(<span><span><span>x1</span>+<span>x2</span></span>2</span>,<span><span><span>y1</span>+<span>y2</span></span>2</span>)</span><span><span>(<span><span><span>x1</span>+<span>x2</span></span>2</span>,<span><span><span>y1</span>+<span>y2</span></span>2</span>)</span><span>
</span></span></span>
Answer:
D. 2x^2-7x.
Step-by-step explanation:
Lets write it out to make it easy to work with.
-x(-2x+7)
Multiply the -x out
2x^2-7x.
The answer is D